Comparison of the Diagnostic Image Quality of the Canine Maxillary Dentoalveolar Structures Obtained by Cone Beam Computed Tomography and 64-Multidetector Row Computed Tomography. (June 2015) - Soukup, Jason W.; Drees, Randi; Koenig, Lisa J.; Snyder, Christopher J.; Hetzel, Scott; Miles, Chanda R.; Schwarz, Tobias
The objective of this blinded study was to validate the use of cone beam computed tomography (CT) for imaging of the canine maxillary dentoalveolar structures by comparing its diagnostic image quality with that of 64-multidetector row CT. Sagittal slices of a tooth-bearing segment of the maxilla of a commercially purchased dog skull embedded in methylmethacrylate were obtained along a line parallel with the dental arch using a commercial histology diamond saw. The slice of tooth-bearing bone that best depicted the dentoalveolar structures was chosen and photographed. The maxillary segment was imaged with cone beam CT and 64-multidetector row CT. Four blinded evaluators compared the cone beam CT and 64-multidetector row CT images and image quality was scored as it related to the anatomy of dentoalveolar structures. Trabecular bone, enamel, dentin, pulp cavity, periodontal ligament space, and lamina dura were scored. In addition, a score depicting the evaluators overall impression of the image was recorded. Images acquired with cone beam CT were found to be significantly superior in image quality to images acquired with 64-multidetector row CT overall, and in all scored categories. In our study setting, cone beam CT was found to be a valid and clinically superior imaging modality for the canine maxillary dentoalveolar structures when compared to 64-multidetector row CT.